Paediatric tonsillectomy in England: A cohort study of clinical practice and outcomes using Hospital Episode Statistics data (2008‐2019). (19th January 2021) - Keltie, Kim; Donne, Adam; Daniel, Mat; Stephenson, Kate; Wyatt, Michelle; Kuo, Michael; Saunders, Michael; Kumar, Nirmal B.; Philpott, Carl M.; Bruce, Iain; Smith, Matthew E.; Hardman, John C.; et al.
Abstract: Objectives: To assess the safety of paediatric tonsillectomy procedures conducted in NHS hospitals in England between 2008 and 2019. Design: Retrospective observational cohort study using Hospital Episode Statistics (HES) data. Setting: Acute NHS trusts in England conducting paediatric tonsillectomy procedures. Participants: Children (≤16 years old) undergoing bilateral tonsillectomy. Main outcome measures: Number of tonsillectomies performed per year by procedural method. In‐hospital complications including return to theatre for arrest of haemorrhage. Readmission within 28 days, including those for pain, haemorrhage and surgical arrest of haemorrhage. Long‐term outcomes: all‐cause mortality, revision tonsillectomy. Results: A total of 318 453 paediatric tonsillectomies were performed from 2008 to 2019:278, 772 dissection (87.5%) and 39 681 coblation (12.5%). The proportion of tonsillectomy performed using coblation increased from 7% in 2008/9 to 27% in 2018/9. Five patients died in hospital (including 4 due to respiratory complications). In‐hospital complications occurred in 4202 children (1.3%), with the most frequent being haemorrhage. Within 28 days of tonsillectomy, 28 170 patients (8.8%) were readmitted and 7 deaths occurred. Readmission rates for haemorrhage and pain have increased since 2008. The proportion of children undergoing revision tonsillectomy procedures within 5 years following coblation tonsillectomy (1.4%) was approximately double that of dissection (0.6%). Conclusions: Clinical practice of paediatric tonsillectomy has changed in England over the past 11 years. The overall mortality rate associated with the procedure is 0.0037%. Differences in outcomes have been identified for different procedural methods. However, routine administrative data are limited in differentiating procedural detail (eg we are unable to differentiate intra or extra‐capsular techniques from current clinical coding of tonsillectomy procedures). Therefore, prospective national data collection or more granular clinical coding is essential to capture relative outcomes of the different tonsillectomy methods and techniques being used in the NHS.